Permanent versus Retrievable Inferior Vena Cava Filters: Rethinking the “One-Filter-for-All” Approach to Mechanical Thromboembolic Prophylaxis - Ghatan, Christine E.; Ryu, Robert K. (Seminars in Interventional Radiology, 2016)
Inferior vena cava (IVC) filtration for thromboembolic protection is not without risks, and there are important differences among commercially available IVC filters. While retrievable filters are approved for permanent implantation, they may be associated with higher device-related complications in the long term when compared with permanent filters. Prospective patient selection in determining which patients might be better served by permanent or retrievable filter devices is central to resource optimization, in addition to improved clinical follow-up and a concerted effort to retrieve filters when no longer needed. This article highlights the differences between permanent and retrievable devices, describes the interplay between these differences and the clinical indications for IVC filtration, advises against a “one-filter-for-all” approach to mechanical thromboembolic prophylaxis, and discusses strategies for optimizing personalized device selection.
Keywords: inferior vena cava filters; optional filter; retrievable filter; complications; patient selection; interventional radiology